The Cambridge companion to international organizations law - Klabbers, Jan (Cambridge University Press, 2022)
The Cambridge Companion to International Organizations Law illuminates, from a legal perspective, what international organizations are, what makes them 'tick' and how they affect the world around them. It critically discusses such classic issues as the concept of international organization and membership, as well as questions of internal relations, accountability and how they make law, set standards and otherwise affect both their member states and the world around them. The volume further discusses the role of international organizations in particular policy domains, zooming in on domains which are not often discussed through international organizations, including disarmament, energy, food security and health. Eventually, a picture emerges of international organizations as complex phenomena engaging in all sorts of activities and relationships, the operation and authority of which is underpinned by the rules and regulations of international law.
Literaturverzeichnis: Seite 426-466, Register
Keywords: Aufsatzsammlung; Recht; Internationale Organisation